The Illusory Formlessness Administrative Proceedings Sanctioning: the Principle of Instrumentality of Ways vs. the Purposes of the Process, under the Auspices of Ethics, Morality and Complexity - Dezan, Sandro; Carmona, Paulo (Revista ANPPREV de Seguridade Social, 2024)
This study seeks to analyze this interrelationship between functions and purposes of the administrative process involving the pursuit of internal control of discipline in the public service and the pseudo-normative mechanisms for managing procedural “illegalities," especially the principle of the instrumentality of forms or moderate formalism, used by case law – and, nevertheless, thus defended by doctrine –, for the maintenance of the effects of illegal procedural, administrative acts given the consideration that it has achieved the purpose that will be obtained with the production of the specific act, legally provided for.